BS ISO 21915-1. Textiles. Qualitative and quantitative analysis of some cellulose fibres (lyocell, cupro) and their blends. Part 1. Fibre identification using scanning electron microscopy and spectral analysis methods (30th August 2019) - British Standards Institution,
No abstract available